2020
DOI: 10.4274/tjo.galenos.2020.77026
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Microbial Keratitis After Penetrating Keratoplasty According to Early and Late Postoperative Periods

Abstract: Objectives: The aim of this study was to investigate the distribution of microbial agents in the early and late postoperative periods in patients with microbial keratitis (MK) after penetrating keratoplasty (PK). Materials and Methods: The records of 36 patients who were clinically diagnosed as having MK after PK were retrospectively reviewed. Culture results were obtained from microbiology records and the organisms that were produced were noted. A case was deemed as vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Infectious keratitis following PKP can occur in the early (<1 year) or late (> 1 year) post-operative period as described by previous studies. 10,16 Chen et al 14 noted that 57.1% of their patients developed graft infection within 1 year of PKP while 46.3% of patients had early graft infection in the study by Sun et al 10 In our study 62.82% patients developed early infection. The possible reasons for higher chance of developing early infections in the graft could be higher dose of topical steroids, presence of multiple sutures, a healing graft-host junction and decreased corneal sensitivity in the first year following PKP.…”
Section: Discussionsupporting
confidence: 50%
“…Infectious keratitis following PKP can occur in the early (<1 year) or late (> 1 year) post-operative period as described by previous studies. 10,16 Chen et al 14 noted that 57.1% of their patients developed graft infection within 1 year of PKP while 46.3% of patients had early graft infection in the study by Sun et al 10 In our study 62.82% patients developed early infection. The possible reasons for higher chance of developing early infections in the graft could be higher dose of topical steroids, presence of multiple sutures, a healing graft-host junction and decreased corneal sensitivity in the first year following PKP.…”
Section: Discussionsupporting
confidence: 50%
“…as the most common causative agent of microbial keratitis following PK. 10,21 Ozlap et al found that 55.5% of cases of microbial keratitis after PK were of bacterial origin, followed by 41.7% viral and 2.8% fungal. 21 This case series identi ed a higher rate of fungal keratitis (33.3%) than reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of microbial keratitis after penetrating keratoplasty without the use of contact lens has been reported as between 1.8% and 12.1%. 21 This makes it di cult to determine any direct causation or correlation between postoperative contact lens wear following PK and the development of infectious keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several well-established risk factors for recurrent infections in therapeutic grafts: fungal origin, big ulcer size (diameter of at least 60 mm), graft size (diameter of at least 8.5 mm), endophthalmitis, limbal involvement, perforated cornea, endothelial or retro-iris exudates [23]. Still, the most common origin of repeated microbial infections is bacteria (>50%), followed by viruses and fungi [60]. The recurrence rate varies from 2-3% to 41% in different analyses [2,23,59,62].…”
Section: Keratitis In Repeated Graftsmentioning
confidence: 99%
“…Table 4 summarizes the available literature on the time of PKMK onset after corneal transplant derived from the last 18 years of original research. Notably, fungal etiology brings about bacterial and viral infections [60]. Interestingly, contaminated donor tissue tends to manifest corneal ulcer early (within the first 2 months) [56].…”
Section: Timementioning
confidence: 99%